Rehabilitation of Fractured Tooth by a Custom Made Fibre Reinforced Composite Post - Mishra,Lora (Universidad de La Frontera. Facultad de Medicina, 2012)
Management of traumatic injuries to the teeth is a challenge to the practising dentist. It has no prescriptive method for occurring, possesses no significant predictable pattern of intensity or extensiveness and occurring at times when dentists are least prepared for it. Ninety-two percent of traumatic injuries results in fracture of maxillary permanent central incisors because its protrusive and anterior positioning. The young permanent maxillary central incisor root canal chamber is large and tapered. This case report describes the management of Ellis Class III fractured tooth in a young permanent maxillary central incisor by an innovative clinical procedure.